Influence of Growth Regulators on Shoot Proliferation and Plantlet Production from Shoot Tips of Banana (Progressive Agriculture, 2013)
The effect of BAP and IBA on in vitro regeneration of four banana cultivars viz. Amritsagar, Seeded banana, Sabri and Anajee was studied. The response of single shoot regeneration from shoot tips of four banana cultivars at different concentrations of BAP was found to be different. The cultivar Amritsagar produced the highest percentage (60 %) of single shoot at 4.0 mg/l BAP within 10-15 days. The cultivar Sabri and Anajee produced lower percentage of single shoots. Rates of shoot multiplication of Amritsagar, Sabri, and Anajee were 6-7 plantlets/explant, 2-4 plantlets/explant, and 2 plantlets/explant, respectively on medium containing 4.0 mg/l BAP after 30 days of culture. But in subsequent subculture, on the same medium, Amritsagar produced the highest number of plantlets (9 plantlets/explant) within the same period of time. The best root formation in multiplied shoots of Amritsagar was found on MS medium containing 2.0 mg/l IBA after 15 days of culture. All the in vitro cultured banana plantlets of Amritsagar survived when weaned to ex vitro conditions on soil.DOI: http://dx.doi.org/10.3329/pa.v20i1-2.16840 Progress. Agric. 20(1 & 2): 9 16, 2009